2012
DOI: 10.1007/s10841-012-9499-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by distance in saproxylic beetles may increase with niche specialization

Abstract: Species confined to temporally stable habitats are usually susceptible to habitat fragmentation, as living in long-lasting habitats is predicted to constrain evolution of dispersal ability. In Europe, saproxylic invertebrates associated with tree hollows are currently threatened due to the severe fragmentation of their habitat, but data on the population genetic consequences of such habitat decline are still scarce. By employing AFLP markers, we compared the spatial genetic structure of two ecologically and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 75 publications
2
52
0
Order By: Relevance
“…The question whether populations of E. ferrugineus living in more fragmented landscapes show weaker dispersal capacity, stronger spatial genetic structure or more elevated inbreeding levels, opens interesting perspectives for further comparative research. Such a pattern was recently found in the beetles of the genus Osmoderma, a main prey of E. ferrugineus larvae, where differences in dispersal distances between populations from different geographic regions of Europe were detected (Ranius and Hedin 2001;Hedin and Ranius 2002;Dubois et al 2010;Oleksa et al 2013a;Chiari et al 2013;Le Gouar et al 2014). Since the dispersal in poikilotherms is strictly dependent on temperature, these differences may be the result of climatic factors, as observed in other insects (Cormont et al 2011;Delattre et al 2013); however, it is also possible that differences in dispersal capacities could be explained by various selective pressures acting on the beetles in landscapes of different connectivity and habitat size.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The question whether populations of E. ferrugineus living in more fragmented landscapes show weaker dispersal capacity, stronger spatial genetic structure or more elevated inbreeding levels, opens interesting perspectives for further comparative research. Such a pattern was recently found in the beetles of the genus Osmoderma, a main prey of E. ferrugineus larvae, where differences in dispersal distances between populations from different geographic regions of Europe were detected (Ranius and Hedin 2001;Hedin and Ranius 2002;Dubois et al 2010;Oleksa et al 2013a;Chiari et al 2013;Le Gouar et al 2014). Since the dispersal in poikilotherms is strictly dependent on temperature, these differences may be the result of climatic factors, as observed in other insects (Cormont et al 2011;Delattre et al 2013); however, it is also possible that differences in dispersal capacities could be explained by various selective pressures acting on the beetles in landscapes of different connectivity and habitat size.…”
Section: Discussionsupporting
confidence: 61%
“…Although our estimates are imprecise due to the lack of knowledge about the effective density and (possibly) its variability over the studied area, dispersal of several hundred meters is highly possible in this species. Zauli et al (2014) found that males of E. ferrugineus moved from the site of first capture covering a median distance of 214 m and approximately 50 % of individuals disperse not further than 250 m. Observed movement distances of other saproxylic beetles could comprise more than 700 m in a species which is believed to be poor flier (Dubois et al 2010;Oleksa et al 2013a) and even more than 10 km for species with high dispersal capacities (Jonsson 2003;Williams and Robertson 2008;Drag et al 2011). In this respect, E. ferrugineus can be regarded as a species with lower dispersal abilities, for which habitat continuity plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other methods, such as population genetic analyses, telemetry, and dispersal simulators (i.e. flight-mills), the MRRbased results tend to give lowest dispersal estimates due to underestimation of long-distance movements (Koenig et al, 1996;Jonsell et al, 2003;Drag et al, 2011;Chiari et al, 2013;David et al, 2013;Oleksa et al, 2013), and vary due to local conditions and/or sampling designs (e.g. Stevens et al, 2010;Hassal & Thompson, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Radio-tracking yielded maximum flight distances of 180m (Hedin et al 2008), 700m (Dubois and Vignon 2008) and 1,504m (Chiari et al 2013). Other techniques confirmed this range of dispersal: 190m (Ranius and Hedin 2001) and 2,090m (Valainis et al 2015) with markrecapture studies, about 500m calculated with DNA markers (Oleksa et al 2013) and a maximum single flight distance of 1,454m and a maximum cumulative flight distance of 2,361m obtained with a flight mill (Dubois et al 2010). Dispersal is probably guided by the (R)-(+)-γ-decalactone, a pheromone emitted by males to attract females and sometimes also males in various other species of Osmoderma (Larsson et al 2003, Svensson et al 2009, Zauli et al 2016.…”
Section: Species Studiedmentioning
confidence: 83%